2020
DOI: 10.1002/mde.3253
|View full text |Cite
|
Sign up to set email alerts
|

Threshold effect of gender composition in the top management team on firm innovation: New evidence from China

Abstract: Whether there is an optimal threshold interval of gender structure of the top management team (hereafter TMT) was determined from the view of maximizing the innovation capacity of the firm. Drawing upon the social role and cognitive theories, the present study applies the panel threshold regression model to reconcile the mixed findings with regard to the relationship between TMT gender composition and enterprise innovation using the data from 187 listed electronic firms in China during the period of 2012–2016.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…According to Social role theory, the gender composition of TMTs is determined by complex social processes arising from human activity and corporate governance (Kirsch, 2018) 10 . In China, men and women play different social roles, which in turn will influence the decision-making and management behavior related to corporate innovation (Huang, 2021) 11 . On the one hand, compared with male executives, women can create an open and relaxed working environment for their teams, which is conducive to improving the company's ability to innovate.…”
Section: Tmts Heterogeneity and Corporate Innovation Performancementioning
confidence: 99%
“…According to Social role theory, the gender composition of TMTs is determined by complex social processes arising from human activity and corporate governance (Kirsch, 2018) 10 . In China, men and women play different social roles, which in turn will influence the decision-making and management behavior related to corporate innovation (Huang, 2021) 11 . On the one hand, compared with male executives, women can create an open and relaxed working environment for their teams, which is conducive to improving the company's ability to innovate.…”
Section: Tmts Heterogeneity and Corporate Innovation Performancementioning
confidence: 99%
“…More recently, research has focused on the relationships between female managers and a range of organizational activities and outcomes (e.g. Horak & Cui, 2017;Huang, 2020).…”
Section: What Has Been Researched On Women In Management In China?mentioning
confidence: 99%
“…Research has also started to consider the creativity consequences of attributes pertaining to demographic diversity at the organizational level. The gender diversities of R&D workforces (Diaz-Garcia et al, 2013), of TMTs (Huang, 2021), and of boards (Ain et al, 2021), just as the age diversity of TMTs (Yoon et al, 2016), were all shown to stimulate organizational creativity. More specifically, the positive effect of a TMT's gender diversity on firm innovation was found for a female-to-male ratio of .25 to .30 but became insignificant and even turned negative for a ratio below .25 (Huang, 2021).…”
Section: Job-unrelated Diversities At the Surface Levelmentioning
confidence: 99%
“…The gender diversities of R&D workforces (Diaz-Garcia et al, 2013), of TMTs (Huang, 2021), and of boards (Ain et al, 2021), just as the age diversity of TMTs (Yoon et al, 2016), were all shown to stimulate organizational creativity. More specifically, the positive effect of a TMT's gender diversity on firm innovation was found for a female-to-male ratio of .25 to .30 but became insignificant and even turned negative for a ratio below .25 (Huang, 2021). Adding to this organizational-level research, the national diversity of TMTs also tends to stimulate organizational creativity by offering a greater variety in external knowledge sourcing strategies, a mediating mechanism that has been shown to be stronger for organizations that had TMTs possessing lower social stratification or that were located in countries characterized by low power distance (Boone et al, 2019).…”
Section: Job-unrelated Diversities At the Surface Levelmentioning
confidence: 99%